Intracameral Versus Sub-conjunctival Dexamethasone Injection for Postoperative Inflammation in Congenital Cataract Surgery - Waseem Akhter, Afia Matloob Rana Ali Raza (Pakistan Journal of Ophthalmology, 2019)
Purpose: To compare the effect of intracameral with sub-conjunctival injection of dexamethasone in preventing immediate postoperative inflammation after congenital cataract extraction. Study Design: Randomized control trial. Place and Duration of Study: Holy Family Hospital, Rawalpindi from June 2014 to May 2015. Material and Methods: All Pediatric patients less than 15 years of age and of both genders, undergoing cataract surgery in Holy Family Hospital, were included in the study using a random table. Using standardized sample size calculator and statistical assumption with 95% CI and 5% alpha error, the study sample was 95 cases in each group. Group A patients got intracameral injection of dexamethasone while Group B patients got subconjunctival injection of dexamethasone. The outcome measure was intraocular inflammation after cataract surgery. Examination was done within first three postoperative days for signs of anterior chamber inflammation. Standard slit lamp or hand held slit lamp was used for this purpose. Results: One hundred and ninety patients were included in the study. The patients were equally divided into 2 groups. Male cases were in majority in group B (58.9%) whereas in group A females (55.8%) were in majority. Mean age was 6.43 ? 4.69 years in Group-A compared to 5.85 ? 4.10 years in Group-B. Frequency of posterior synechiae (inflammation) was 4.21% (n = 4) in Group-A (intracameral) compared to 15.79% (n = 15) in Group-B (subconjunctival) which was significantly different (p-value = 0.007). Conclusion: Intracameral injection is better than sub-conjunctival injection of dexamethasone in the management of post-operative inflammation in children with congenital cataract. Keywords: Congenital cataract, Dexamethasone, Injections, Inflammation.